The study of level of freight forwarders’ satisfaction towards MASkargo Sdn Bhd / Nur Farezza Zainal - Zainal, Nur Farezza (2011)
The purpose of this study is to examine the level of freight forwarders’ satisfaction toward MASkargo Sdn. Bhd. The respondents are the freight forwarders at ACC, MASkargo itself. The problem that MASkargo faces is increasing number of cancelation on space booked by freight forwarders since 3nd quarter of 2009. The objectives of this research are to examine the level of freight forwarders’ satisfaction towards MASkargo, to examine the most dominant factor of freight forwarders’ satisfaction towards MASkargo and to give the recommendations to increase the level of freight forwarders’ satisfaction towards MASkargo. For the research methodology, researcher used Exploratory and Descriptive Research in conducted this research study. The populations in this study are the freight forwarders at MASkargo. Convenience Sampling is used as sampling technique. The number of respondent is 30 respondents. In this study, primary data is used to collect data using survey data collection method, which is questionnaire. Data collected will analyze using Statistical Package for the Social Science (SPSS) for Windows. The methods will use Reliability Test and Frequency Distribution Analysis. For Reliability Test, Cronbach’s Alpha will use to measure the consistency reliability of data. Frequency Distribution Analysis will use to find frequency of respondents’ profile which it describes the frequency characteristics of the respondents. The finding for identifying the level of freight forwarders’ satisfaction towards MASkargo is 3.87. For the result to rank the most dominant factors of freight forwarders’ satisfaction, MASkargo’s service quality is the factor that most affecting the freight forwarders’ satisfaction towards MASkargo Sdn. Bhd.